Rethinking Yang Wenhui’s identity as a ‘Chinese’ Pure Land Buddhist in his polemics against Jōdo-Shinshū - Zamorski, Jakub (2020)
In this article I would like to re-examine the doctrinal debate that ensued between the Chinese Buddhist layman and scholar Yang Wenhui (1837-1911) and Japanese priests of the Jōdo-Shinshū 淨土真宗 school - notably Ogurusu Kōchō (1831-1905) and Naiki Ryūsen (1861-1922) - between 1899 and 1901. The debate in question has been most often portrayed as a clash between two divergent understandings of Pure Land Buddhism that developed independently of each other in China and Japan. Yang’s arguments have been taken to illustrate larger exegetical and doctrinal tendencies characteristic of the ‘Chinese’ approach to the Pure Land, regarded as quite foreign to Japanese readers. However, as will be argued below, Yang did not participate in this debate merely as a spokesman for a putative generalized ‘Chinese’ Pure Land Buddhism; he was also an apologist who weighed in the ongoing domestic Chinese debates on the Pure Land, and a reformist who played a pivotal role in the process of negotiating a modern orthodoxy for the so-called ‘Pure Land tradition’ of China.
Keywords: Ogurusu Kōchō; Pure Land Buddhism; Yang Renshan; Yang Wenhui